Impact of Combining Long-Term Subsoiling and Organic Fertilizer on Soil Microbial Biomass Carbon and Nitrogen, Soil Enzyme Activity, and Water Use of Winter Wheat - Yang, Yonghui; Li, Minjie; Wu, Jicheng; Pan, Xiaoying; Gao, Cuimin; Tang, Darrell W. S. (Frontiers in Plant Science, 2022)
Reductions in soil productivity and soil water retention capacity, and water scarcity during crop growth, may occur due to long-term suboptimal tillage and fertilization practices. Therefore, the application of appropriate tillage (subsoiling) and fertilization (organic fertilizer) practices is important for improving soil structure, water conservation and soil productivity. We hypothesize that subsoiling tillage combined with organic fertilizer has a better effect than subsoiling or organic fertilizer alone. A field experiment in Henan, China, has been conducted since 2011 to explore the effects of subsoiling and organic fertilizer, in combination, on winter wheat (Triticum aestivum L.) farming. We studied the effects of conventional tillage (CT), subsoiling (S), organic fertilizer (OF), and organic fertilizer combined with subsoiling (S+OF) treatments on dry matter accumulation (DM), water consumption (ET), water use efficiency (WUE) at different growth stages, yield, and water production efficiency (WPE) of winter wheat over 3 years (2016–2017, 2017–2018, 2018–2019). We also analyzed the soil structure, soil organic carbon, soil microbial biomass carbon and nitrogen, and soil enzymes in 2019. The results indicate that compared with CT, the S, OF and S+OF treatments increased the proportion of >0.25 mm aggregates, and S+OF especially led to increased soil organic carbon, soil microbial biomass carbon and nitrogen, soil enzyme activity (sucrase, cellulose, and urease). S+OF treatment was most effective in reducing ET, and increasing DM and WUE during the entire growth period of wheat. S+OF treatment also increased the total dry matter accumulation (Total DM) and total water use efficiency (total WUE) by 18.6–32.0% and 36.6–42.7%, respectively, during these 3 years. Wheat yield and WPE under S+OF treatment increased by 11.6–28.6% and 26.8–43.6%, respectively, in these 3 years. Therefore, S+OF in combination was found to be superior to S or OF alone, which in turn yielded better results than the CT.